2007
DOI: 10.1152/jn.01189.2006
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Induces Memory-Like, Rapamycin-Sensitive Hyperexcitability in Sensory Axons ofAplysiaThat Contributes to Injury Responses

Abstract: The induction of long-term facilitation (LTF) of synapses of Aplysia sensory neurons (SNs) by serotonin (5-HT) has provided an important mechanistic model of memory, but little is known about other long-term effects of 5-HT on sensory properties. Here we show that crushing peripheral nerves results in long-term hyperexcitability (LTH) of the axons of these nociceptive SNs that requires 5-HT activity in the injured nerve. Serotonin application to a nerve segment induces local axonal (but not somal) LTH that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 80 publications
2
17
0
Order By: Relevance
“…This is consistent with the large body of work showing overlap in the mechanisms of long-term sensitization and hyperalgesia (e.g. Walters, 1987; Weragoda & Walters, 2007). We are now testing if pharmacological inhibition of GlyT2 can block the induction or maintenance of long-term sensitization memory.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with the large body of work showing overlap in the mechanisms of long-term sensitization and hyperalgesia (e.g. Walters, 1987; Weragoda & Walters, 2007). We are now testing if pharmacological inhibition of GlyT2 can block the induction or maintenance of long-term sensitization memory.…”
Section: Discussionsupporting
confidence: 90%
“…Some of the general initiating signals that are common to molluscan and mammalian nociceptors, and to neurons displaying long-term plasticity in central neurons of diverse animals are shown in figure 3 . Initiating events for long-term alterations include intense depolarization and Ca 2+ entry consequent to membrane injury or binding of excitatory amino acids, and activation of cell signaling pathways by binding of neuromodulators and growth factors released by neurons [Jankowsky and Patterson, 1999;Kandel, 2001;Weragoda and Walters, 2007] and other cell types [e.g., glia, support cells, and inflammatory cells; Bradley and Finkbeiner, 2002;Gibbs et al, 2008]. Changes in gene expression are triggered by Ca 2+ entry accompanying action potentials propagating into the soma [Saha and Dudek, 2008], as well as retrograde signals transported to the nucleus from sites of axonal injury [Gunstream et al, 1995;Lin et al, 2003; or intense synaptic stimulation [Otis et al, 2006;Lai et al, 2008].…”
Section: Did Fundamental Mechanisms Underlying Memory and Chronic Paimentioning
confidence: 99%
“…Further experiments would need to be conducted in Aplysia to determine whether this was the case for the axons in p9. The potential of 5-HT release in the nerve is significant because 5-HT has been implicated as mediating responses to injury in the nerve (Weragoda and Walters 2007). 5-HT might be taken up in the periphery, transported along the axon to be released at varicosities in the nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work showed that electrical stimulation of the tail or just the tail nerve, pedal nerve 9 (p9), causes sensitization of the tail withdrawal reflex (Philips et al 2011), the release of 5-HT (Marinesco and Carew 2002), and evokes cellular analogs of behavioral sensitization (Walters et al 1983). Crushing sensory axons in p9 causes long-term hyperexcitability of the axons, which resembles the effects of sensitization and requires 5-HT (Weragoda and Walters 2007). Despite the importance of 5-HT to these studies, the neurons that release 5-HT in response to stimulation or injury of p9 have not been identified.…”
Section: Introductionmentioning
confidence: 99%